Digital Media Design as Information for Art and Cultural Community - Irma Rochmawati; Yulis Syam Fajrilah (Proceeding of International Conference on Business, Economics, Social Sciences, and Humanities, 2023)
Community is an association based on geographic location, similarity in cultural, ideological, socio-economic backgrounds and interest in the same object. One example is the regional community where this community is established because of the similarities in ideology and geographical location. In its development, regional communities have goals, one of which is to develop arts and culture in the area. The purpose of this research is to introduce the regional community in Indonesia, namely Jatiwangi Art Factory. Jatiwangi Art Factory is a cultural arts community that focuses on discussing local rural life. This community is active in activities with the surrounding community but does not provide information about the existence of the Jatiwangi Art Factory community to the community. Many people have participated in the events that this community holds, but the Indonesian people in particular are not familiar with this community. There needs to be an adjustment in communication between communities in delivering information so that this community can truly enter into the lives of the surrounding community. The results of this study are expected to be able to recognize the local community of art and local culture so as to create sustainability of the culture of the community itself. Through several stages of methods to produce information media works in digital form that can introduce the Jatiwangi Art Factory community.